2023
DOI: 10.1182/bloodadvances.2023011096
|View full text |Cite
|
Sign up to set email alerts
|

Application of R2-ISS risk stratification to patients with multiple myeloma treated with autologous stem cell transplants at UAMS

Wancheng Guo,
Anne Zhan,
David E. Mery
et al.

Abstract: R2-ISS was published in 2022 and has been validated in several cohorts of myeloma patients. In this study, we investigated a total of 1007 multiple myeloma (MM) patients who received autologous stem cell transplantation (ASCT) between 2001 and 2021. The median age of the patients was 61 years, with a median overall survival (OS) of 91 months and median progression-free survival (PFS) of 66 months. We collected the variables included in the R-ISS and R2-ISS system, as well as additional data such as routine blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Similar single-center studies have also evaluated the performance of R2-ISS in cohorts from China and Japan [ 11 , 12 ]. An analysis in the United States has validated R2-ISS, but this was in a transplanted cohort, different from our analysis, which was predominantly in a non-transplant cohort [ 13 ].…”
mentioning
confidence: 73%
“…Similar single-center studies have also evaluated the performance of R2-ISS in cohorts from China and Japan [ 11 , 12 ]. An analysis in the United States has validated R2-ISS, but this was in a transplanted cohort, different from our analysis, which was predominantly in a non-transplant cohort [ 13 ].…”
mentioning
confidence: 73%
“… 111 These observations showed that R2-ISS is a reliable prognostic tool for MM patients who received standard anti-myeloma treatment and upfront auto-HSCT. 112 …”
Section: Mutational Landscape Of MMmentioning
confidence: 99%